(3deY GdbhGfjf GdeVjI aj OhGhjf GdOjGQ GdeUQjIs - (3YKeGf Hf EHQGgje GdfGHdSj GdUaOj, aNQ GdOjf,J (B685 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa YHGOg HeNGWHJg s
(3LYd GdeDda GdcJGH Ydi ebOeI hNeSI CHhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B202 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B249s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B335 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B225 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(2022) s
Keywords: (3GdJGQjNs